Efektivitas Air Perasan Jeruk Nipis (Citrus aurantifolia) dalam Menghambat Pertumbuhan Escherichia coli - Ratih Dewi Dwiyanti; hana nailah; Ahmad Muhlisin; Leka Lutpiatina (Jurnal Skala Kesehatan, 2018)
Lime (Citrus aurantifolia) can be used for cough medicine, sputum laxative, influenza, and acne medication. Lime contains useful chemical compounds, one of which is essential oils and flavonoids which function as antibacterials and play a very important role in inhibiting bacterial growth. The purpose of this study was to determine the effectiveness of lime juice (Citrus aurantifolia) at a concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% on the growth of Escherichia coli in vitro. This research is experimental with post test only control group design. The research sample was lime juice. Antibacterial power testing using well diffusion method. Antibacterial power parameters were determined by measuring the inhibitory zone (mm) formed around the growth of test bacteria on Muller Hinton Agar media. The results of the study showed that lime juice inhibition zones against the growth of Eschericia coli at concentrations of 40%, 50%, 60%, 70%, 80%, 90% and 100% were 7.25mm, 13.25mm, 14.25mm, 16mm, 17mm, 18.25mm, and 20.75mm. Based on linear regression test obtained significant value of 0.000 <α 0.05 so it can be concluded that there is an effect of lime juice on Eschericia coli growth in vitro. It is recommended that further research be carried out to test the inhibitory power of lime juice using other methods or against bacteria of other species.